2008
DOI: 10.1071/ea08119
|View full text |Cite
|
Sign up to set email alerts
|

Genetic parameters for bodyweight, wool, and disease resistance and reproduction traits in Merino sheep. 1. Description of traits, model comparison, variance components and their ratios

Abstract: Both wool and sheep meat industries are interested in sheep that have a high reproduction performance and are resistant to internal parasites, in addition to the traditional traits. There is considerable interest in breeding sheep for wool, carcass, reproductive and internal parasite resistance traits simultaneously. The objective of this study was to estimate single trait genetic parameters for 40 traits recorded in Merino sheep, covering bodyweight, carcass, wool, reproduction and internal parasite resistanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
16
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 17 publications
8
16
1
1
Order By: Relevance
“…In general, the heritability estimates found in the present study agree well with estimates from Australian sheep flocks (Safari et al 2005;Huisman et al 2008), indicating that these traits will respond to selection. The heritability estimates for proportion of fibres below 15 micron and for proportion of fibres above 30 micron were 0.59 and 0.45, respectively.…”
Section: Wool Traitssupporting
confidence: 80%
“…In general, the heritability estimates found in the present study agree well with estimates from Australian sheep flocks (Safari et al 2005;Huisman et al 2008), indicating that these traits will respond to selection. The heritability estimates for proportion of fibres below 15 micron and for proportion of fibres above 30 micron were 0.59 and 0.45, respectively.…”
Section: Wool Traitssupporting
confidence: 80%
“…There were high heritability estimates for the major wool production and wool quality traits whereas other wool quality, wool color, and visual traits were more moderately heritable, which is consistent with the review of Safari et al (2005) and more recent reports from several large Merino data sets (Asadi Fozi et al, 2005;Safari et al, 2007;Huisman et al, 2008;Swan et al, 2008Brown et al, 2010Brown et al, , 2013.…”
Section: Heritabilitysupporting
confidence: 74%
“…However, effective breeding programs require information on the genetic relationships between these selection traits and the meat traits measured in the carcass as well as with wool traits. Although several consistent estimates of the genetic variation exist for the major wool and meat production traits (Safari et al, 2005(Safari et al, , 2007Greeff et al, 2008;Huisman et al, 2008;, there are few estimates of genetic correlations between wool and meat traits, particularly for Merino sheep. This second paper of a series reports estimates of genetic and phenotypic correlations between several wool production and quality traits and carcass meat traits, including lean meat yield and the weight of various cuts, from Merino sheep in the Information Nucleus (IN; Fogarty et al, 2007;van der Werf et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Kelly et al (1996) showed that in comparison to progeny from single-bearing ewes fed to maintain maternal liveweight during pregnancy, genetically identical progeny from ewes fed to lose 10 kg between Days 50 and 140 of pregnancy produced~0.14 kg less clean wool that was alsõ 0.1-mm broader at their hogget shearing. These differences in clean fleece weight and fibre diameter between single-born progeny were permanent (Kelly et al 2006), and this is consistent with the differences in wool production and quality that persist between single-and twin-born lambs until at least 2-3 years of age (Huisman et al 2008).…”
Section: Introductionsupporting
confidence: 59%
“…By contrast, while birth-type effects on fibre diameter of wool produced by progeny generally persisting to maturity rear-type effects were only evident at hogget age. Few studies have reported the effects of birth type or rear type on clean fleece weight and fibre diameter beyond 2-3 years (Huisman et al 2008).…”
Section: Discussionmentioning
confidence: 99%